Isolation and Activity Test of Lipolitic Bacteria on Different pH and Temperature - Prapti Sedijani; Dewa Ayu Citra Rasmi; Kusmiyati Kusmiyati; Miko Eniarti; Siti Rohimah (Jurnal Biologi Tropis, 2022)
Lipase is an enzyme that can be applied in many industrial fields so it has a good economic prospects. The demand for lipase was still unfulfilled at the time this article was written. The character of the lipase for industrial needs are vary depending on the industry in which the enzyme is used. Temperature and pH are the two factors that most influence enzyme activity. This article reports on bacteria isolated from coconut, avocado, tempeh, and areca nut and their lipolytic activity at pH 7-10, 30-40oC. Isolation was carried out on NA media supplemented with olive oil and Rhodamine B as the activity indicator. Colonies showing clear zones were used in subsequent work. Activity tests were carried out on the isolation medium pH 7-10 and incubated at 30 or 40oC. Characterization of isolates includes morphological and microscopic observations; proteolytic and amylolytic capability. There were 41 isolates showing lipolytic activity, 26, 7, 4, and 4 isolates from coconut, tempeh, avocado, and areca nut, respectively. Five isolates were selected for further work. Activity tests showed that the best isolates at 30oC were K1A1 and K1A2 at pH 7, each of which had an activity index of 9% and 107%. Meanwhile, at 40oC the best activity was shown by K10 pH 8 with an activity index of 59%. Based on Grams staining and microscopic analysis, isolates belong to Gram-positive coccus bacteria. Isolate K1A1 showed proteolytic and amylolytic activity, K1A2 showed high proteolytic activity but not amylolytic, while K10 did not show both activities.